Floor and ceiling effects of the World Health Organization Disability Assessment Schedule 2.0 among patients with chronic musculoskeletal pain - Katajapuu N.; Laimi K.; Heinonen A.; Saltychev M. (NLM (Medline), 2022)
The aim of this study was to investigate the floor and ceiling effects of 12-item World Health Organization Disability Assessment Schedule 2.0 (WHODAS). This was a cross-sectional survey study at a university’s physical and rehabilitation medicine outpatient clinic of 1988 patients with chronic musculoskeletal pain. Floor and ceiling effects were calculated as relative frequencies of the lowest or the highest possible scores for each item. The probit plotting method was used to detect the non-normality of distribution of the total score graphically. A significant floor effect of 15–79% was observed in all 12 WHODAS 2.0 items. A substantial floor effect for total score was also detected graphically. No ceiling effects were observed. In this study, a significant floor effect was found for all WHODAS 2.0 items among patients with chronic musculoskeletal pain associated with mild or no disability.